Simulasi Kendali Daya Reaktor Nuklir dengan Teknik Kontrol Optimal - Tadeus, Dista Yoel; Setiyono, Budi; Setiawan, Iwan (Departemen Teknik Elektro, Universitas Diponegoro, 2010)
Nuclear reactors is one of systems that have complex characteristics. To control the reactor power optimally, it needs an effective and efficient control system design. Optimal control system is designed based on the method of state feedback to provide optimum control signal based on predetermined performance index. Nuclear reactor dynamics are modeled by mathematical equations as an approach to model of real reactor. Power reactor to be controlled is modeled by a point kinetics method with one group of delay neutrons. Optimal control system design and simulation of the response of a nuclear reactor is accomplished using MATLAB. In the Linear Quadratic Regulator (LQR) control scheme with various value of q and r, the fastest response of control system in order to regulate output of the system occur at q=0,0001 and r=20. In the LQI control scheme with various value of wo, the fastest response of the system to reach the reference occur at wo=1 where q=0,0001 and r=10. LQG control scheme with Tracking System is able to make the reactor power output to set point after the disturbance applied to system. Keyword : Nuclear Reactor, Optimal Control, Kalman Filter